Set-off - Derham, Rory (Clarendon Press, 1996)
received little attention despite its undoubted importance to the legal and business community. The book is based primarily upon English case and statute law though it usefully covers significant case law developments in Australian and New Zealand law and also extends to coverage of international and cross-border set-offs